Development of flexible competencies in the process of physical education classes in the educational space of higher education - Novikova A.A.; Mekhrishvili L.L. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determine the relationship between the approaches to physical education employed in the classroom at a higher technical institution and the development of students’ adaptable skills. Methods and structure of the study. Within the context of the project «Enhancing the adaptive abilities of students» at the Tobolsk Industrial Institute, a research was conducted to assess the level of development of the elements of «soft» skills through physical education. The study involved 110 students from the second and third years of study. Results and conclusions. The investigation showed that the educational approaches and techniques employed in physical education classes contribute to the enhancement of students’ abilities to collaborate effectively, fostering a sense of responsibility for their actions. Additionally, these approaches promote the development of cognitive and creative skills in tackling both specific and general tasks through exercises and participation in sports activities, such as chess tournaments and mini football matches. Furthermore, they cultivate the ability to make informed decisions and achieve desired outcomes.